How and to What Extent Can Islamic Banking and Finance Contribute to Economic Development and Financial Stability and a Comparative Analysis on the Ethical and Social Mobility of Islamic Banks to Conventional Banks - Fernandes, Theresa Joseph (2016)
Banks the most significant and dominant financial sector play essential role in monetary development of nation. The two broad subdivisions of banking sector are Islamic and Conventional banks. Conventional banking activities are driven by synthetic principles whereas Islamic banking activities driven by religious principles. The catastrophizes of global financial crisis due to reckless banking and financial practices of the conventional banks that led to major economic downturn thus brought an urgent need for stable financial system built on real economy. This financial crisis witnessed resilience of Islamic Banking Industry being least affected by such economic downfall, possessing capability of representing itself as steadfast alternative to Conventional Banking system. It’s also maintained if Islamic financial services operated on larger-scale financial crisis wouldn’t have occurred, as grounds for such crisis being reckless banking and lending practices, high liquidity etc. are prohibited in functionalities of Islamic banking. Post financial crisis Islamic financial industry is growing rapidly being inclined towards fulfilling financial duties within religious boundaries. As Islamic finance helps to restore and maintain financial stability worldwide, evidences propose it’s successful in building trust among customers but a lack of awareness of its banking practices prevails. This study analyses mechanism of Islamic banking and financial institutions and highlights the similarities and differences of Islamic to conventional banking system. In this management project, in-depth study examines Islamic banking as alternate mode of financing with comparative analysis between performance of Islamic and Conventional banks to attain profitability and to what extent Islamic Finance contributes to economic financial stability. Besides, corporate ethics has gained alot of importance in financial arena resulting an increase of ethical banking practices. Also investors are aware of this association of ethics and financial investment and are inclined towards benefits of an ethically responsible investment. There are indications Islamic banking being practiced considerably and products and service are accepted in Muslim and non-Muslim countries as main objective of Islamic banking is eradicating exploitation and seeking justice in financial and business activities. The characteristics led to establishment of Islamic finance have greater influence on its ethical and social practices. Thus aim of this management project is to analyse the ethical and social practices of Islamic banks, to what extent its ethical principles and implemented in financial practices being a conceptual effort. Also thesis will further examine appropriate literatures establishing affiliation between concept of Islamic banks and concept of social wellbeing. In conclusion project study will examine contribution of Islamic banking in generating returns, enabling financial stability and overall global economic growth with ethical and social mobility practices